EOSINOPHILIA AS A PREDICTOR MORBIDITY OF SOIL- TRANSMITTED HELMINTHIASES AMONG WIDODAREN PLANTATION WORKERS IN JEMBER - Primadana, Aditya; Nurdian, Yudha; Agustina, Dini; Hermansyah, Bagus; Armiyanti, Yunita (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: Helminthiasis is a neglected tropical disease and still remain a health problem in tropical and sub-tropical countries, including Indonesia. According to WHO, approximately 1,5 billion people or 24% of the world's population, are infected with Soil-Transmitted Helminth (STH). Morbidity is directly related to the intensity of STH infestation. Some of the studies shown a significant correlation between eosinophilia and helminthiasis. Eosinophilia on the blood smear examination may be used as a marker of STH infestation. Purpose: to determine the correlation between Soil-Transmitted Helminthiases and eosinophilia as a predictor of morbidity of STH infestation among Widodaren Plantation Workers in Jember. Method: This observational analytical study use the Kato-Katz method to determine infestation of STH and its intensity measured by egg count per gram stool (EPG). Blood smear examination stained with Giemsa conduct to determine eosinophil count. Result: Prevalence of STH infestation was 22,7% (15/66). Ascaris lumbricoides infection was 13,6% (9/66) and Hookworm infection was 4,5% (3/66). There is mixed infection between A. lumbricoides and Hookworm, the prevalence was 4,5%% (3/66). All of the infection intensity was light. The prevalence of eosinophilia was 27,2% (18/66). There was a significant correlation between STH infection and eosinophilia (P=0,000) but, there was a very weak correlation between the intensity of STH infection and eosinophilia (r=0,281; p=0,258). Conclusion: The prevalence of STH infection among Widodaren Plantation Workers is 22,7% and predominated by A. lumbriocides. There is a positive correlation between intensity of STH infection and eosinophilia as predictor morbidity of STH infection with very weak power.